Women in Lithuanian School Management: An Ethnographic Perspective - Bairašauskienė, Lina (Acta Paedagogica Vilnensia, 2020)
The research takes on a transdisciplinary approach, focusing on paths of how female school principals construct and develop professional identity. Two major approaches to professional identity include a feminist standpoint and a social constructionist approach. The former claims are that females are underrepresented as leaders in most facets of work life due to gender role stereotypes, prejudices, and unequal power distribution. The latter subscribes to the notion that a person’s identities are multiple and fluid due to their cultural, historic, and social situatedness. According to a feminist standpoint, female identities are developed very differently from their male counterparts as a systemic hierarchy of inequity above the principalship is recognized. Despite the fact that the number of female school principals has been growing in the field of education management, a masculine approach is still being applied in this sphere due to the prevailing dominance of power culture in the society. The study is framed as an ethnographic case study. It aims to understand, investigate, and discover the patterns of how professional identity, as a cultural construct, is acquired in the context of concepts of agency, power relations, subjectivities within gender, and social analysis, encompassing multiple interactions in institutionalized processes and systems by which they are formed, shaped, and reshaped over time.